Comparison between Poaceae Airborne Pollen Counts and Phl p5 Aeroallergen Quantification in South Europe - Antunes, Celia M. (2010)
The European project HIALINE: Comparison between Poaceae Airborne Pollen Counts and Phl p5 Aeroallergen Quantification in South Europe C. Antunes1,2, R. Ferro2, R. Ribeiro2, Torres M.C.4, M.J. Velasco4H. García-Mozo4, Galán, C4 , R.Brandao1,3, M.Thibaudon5, R. Albertini6 Ugolotti. M.6, Usberti I.6, Dall’Aglio P.6 and the HIALINE team7 1DInstitute of Mediterranean Agricultural and Environmental Sciences –ICAAM, University of Évora, Portugal 2Department of Chemistry, University of Évora, Portugal 3Department of Biology, University of Évora, Portugal 4Department of Botany, Ecology and Plant Physiology, University of Córdoba 5Réseau National de l Surveillance Aerobiologique, Saint-Genis-l’Argentière, France 6Department of Clinical Medicine, Nephrology and Health Sciences, University of Parma, Italy 7J.T.M. Buters, Germany, M. Thibaudon, France, M. Smith, Great Britain, C. Galan, Spain, R. Brandao and C.M. Antunes, Portugal, G. Reese, Germany, R. Albertini, Italy, L. Grewling, Poland, A. Rantio-Lehtimäki, Finland, S. Jäger and U. Berger, Austria, I. Sauliene, Lithuania, L. Cecchi, Italy Introduction: Nowadays, pollinosis is affecting a large percentage of population in countries with a western life style. The existence of allergenic activity in the atmosphere is not only associated to pollen grains and fungal spores, but also to submicronic and paucimicronic biological particles. The origin of these allergens can be due to the rupture of pollen transported in the atmosphere or to the presence of allergens from other parts of the plant making amorphous material with an allergen load. Poaceae pollen is recognized as one of the main causes of allergic disease in all Europe. In this study we have tried to compare Poaceae pollen counts in the air and Phl p 5, one of the major allergens of this family, through the use of a high-volume cascade impactor (Chemvol). This study was done in the frame of the European project HIALINE and it compares the results obtained in 2009 by 4 different partners participating in this project: in Córdoba (Spain), Évora (Portugal), Lyon (France) and Parma (Italy). Methodology: Pollen grains were sampled using a 7-day volumetric Hirst type spore trap. Chemvol high-volume cascade impactor equipped with stages PM>10µm, 10 µm>PM>2.5µm was used for detecting aeroallergens. In each stage polyurethane filters were use as an impacting substrate. Phl p 5 allergen was determined using an allergen specific ELISA. Antibodies for analysis were delivered by Allergopharma Joachim Ganzer KG, the industrial partner in this project. At each location both samplers were placed side-by-side. Results: Most of the allergen was collected in the PM>10µm fraction. Similar profiles between airborne pollen and the total allergenic load was observed during the pollen season. A good correlation was obtained between pollen count and allergen content of the air and a value of 2.5 pg/pollen grain of Poaceae was estimated. Discussion: This is the first year of this project. Nevertheless, results suggest that the allergenic load in outdoor air might be mainly due to pollen bursts. It supports the hypothesis that monitoring the allergens itself in ambient air might be an improvement in allergen exposure assessment. This work was supported in part by the European Agency for Health and Consumers EAHC, Luxembourg, under the grant agreement 20081107